Sarcopenia and Post-Operative Morbidity and Mortality in Patients with Gastric Cancer - O'Brien, Stephen (J Gastric Cancer, 2018)
PURPOSE: Surgical resection for gastric adenocarcinoma is associated with significant post-operative morbidity and mortality. The aim of this study was to assess the prognostic significance of sarcopenia in patients undergoing resection for gastric adenocarcinoma with respect to post-operative morbidity and survival. MATERIALS AND METHODS: A retrospective analysis was conducted on a cohort of consecutive patients who underwent surgical resection for gastric adenocarcinoma between 2008 and 2014. Patient demographics, radiological parameters, and pathological data were collected. OsiriX software (Pixmeo) was used to measure skeletal muscle area, which was normalized for height to calculate skeletal muscle index. RESULTS: A total of 56 patients (41 male, 15 female; mean age, 68.4 ± 11.9 years) met the inclusion criteria. Of these, 36% (20 of 56) of the patients were sarcopenic pre-operatively. Both sarcopenic and non-sarcopenic patient groups were equally matched with the exception of weight and body mass index (P=0.036 and 0.001, respectively). Sarcopenia was associated with a decreased overall survival (log-rank P=0.003) and was an adverse prognostic predictor of overall survival in multivariate analysis (hazard ratio, 10.915; P=0.001). Sarcopenia was a predictor of serious in-hospital complications in multivariate analysis (odds ratio, 3.508; P=0.042). CONCLUSIONS: In patients undergoing curative resection for gastric cancer, there was a statistically significant association between sarcopenia and both decreased overall survival and serious post-operative complications. The measurement and reporting of skeletal muscle index on pre-operative computed tomography should be considered.